Identification of QTLs for tolerance to hypoxia during germination in rice - Kim, Suk-Man; Reinke, Russell F. (Springer, 2018)
Direct seeding of rice as a method of crop establishment is increasingly being adopted by farmers as a means of saving labor and reducing costs. However, the method often results in a poor environment for germination as excessive water levels after seeding can cause poor seedling establishment and a concomitant reduction in yield potential, especially in submergence-prone areas. In this study, we discovered QTLs associated with tolerance of anaerobic germination (AG) in new genetic accessions using genotypic data derived from the Illumina 6K SNP chip. The mapping population developed for QTL analysis comprised 285 F2:3 plants derived from a cross between Tai Nguyen and Anda. In order to evaluate AG tolerance within the mapping population, phenotyping was carried out under anaerobic conditions for 21 days. Three QTLs associated with AG tolerance were identified in the population, qAG1a and qAG1b on chromosome 1 and qAG8 on chromosome 8 using composite interval mapping (CIM). The percentage of variance explained by these QTLs ranged from 5.49 to 14.14%. The lines with three QTLs (qAG1b + qAG1a + qAG8) demonstrated an approximate 50% survival rate under anaerobic conditions, while lines with two QTLs including qAG1b demonstrated survival rates of 36 and 32% after the treatment, respectively. The QTLs detected in this study may be used to improve AG tolerance during germination and may be combined with other QTLs for anaerobic germination to enhance adaptation to direct seeding and to broaden the understanding of the genetic control of tolerance of germination under anaerobic conditions.